Symptom variation and disease severity of Sweet potato leaf curl virus on sweet potato in Gianyar - Ni Kadek Sattvika Griyaningsih; Listihani Listihani; I Gusti Ayu Diah Yuniti; Putu Lasmi Yulianthi Sapanca; Ni Putu Eka Pratiwi; Ni Putu Pandawani; Dewa Gede Wiryangga Selangga (Agrovigor, 2023)
Sweet potato production fluctuates every year, one of the factors causing the decline in production is the presence of pests and diseases. Sweet potato leaf curl virus (SPLCV) has been reported to infect sweet potatoes in Indonesia in 2022. Until now, there is no information regarding the variation in symptoms and severity of SPLCV disease in sweet potatoes. Therefore, this study aims to analyze the variation in symptoms and severity of SPLCV disease in Gianyar, Bali. The research was carried out directly in the field with observational parameters such as symptoms variation, incidence and disease severity. Observations were made every week when the plants were 63 to 91 days after planting (DAP). The results showed that SPLCV causes a variety of symptoms in the form of mild vein clearing, severe vein clearing, upward vein clearing, and downward vein clearing. The incidence and severity of the disease has increased every week. The incidence and severity of the disease were highest when the plants were 91 DAP, namely 73.33% and 40%, respectively. The high incidence and severity of the disease in the field is due to the use of stem cuttings from previous plants which may have been infected with SPLCV and whitefly vectors are always found in the field.